A Novel Mutation in the Adult-Onset Alexander’s Disease GFAP Gene - Dhillon B. Zaver; Nathan T. Douthit (Case Reports in Medicine)
The case describes a 25-year-old Caucasian female diagnosed with Alexander’s disease (AxD) as an outpatient after extensive inpatient workup. Her presenting complaints included incontinence, clumsiness, seizures, dysphagia, and dysarthria. She was also found to have pancytopenia and dysautonomia. A full neurologic and hematologic workup yielded very little results, until a thorough literature search of her presenting complaints and radiologic findings pointed to adult-onset Alexander’s Disease. Alexander’s disease is a rare genetic leukodystrophy with a broad variety of presentations. Despite its infrequency in adults and the difficulty in diagnosis, the prevalence of AxD has been increasing due to ease of genetic analysis and identification of key clinical and radiological findings. This case illustrates the necessity of vigilance and persistence in the face of unusual patient presentations; occasionally, the sound of hoofbeats is zebras.